Shifts in community‐level traits and functional diversity in a mixed conifer forest: a legacy of land‐use change. Issue 6 (29th July 2016) - Strahan, Robert T.; Sánchez Meador, Andrew J.; Huffman, David W.; Laughlin, Daniel C.
Summary: Historical reference conditions have long been used to guide the restoration of degraded ecosystems. However, a rapidly changing climate and altered disturbance regimes are calling into question the usefulness of this approach. As a consequence, restoration goals are increasingly focused on creating communities that are resilient to novel environmental stressors and emphasis is being placed on defining functional targets through the use of plant traits. While changes in forest structure and composition have received much attention, long‐term changes in stand‐level functional traits are not well understood. We used dendrochronology to reconstruct historical forest structure and composition in 1880, the year immediately following the disruption of the natural fire regime in a mixed conifer forest in Arizona, USA. We analysed the differences in pre‐settlement and contemporary forest composition, structure and community‐weighted mean (CWM) traits, and functional diversity metrics (Rao's Q and functional richness) for four plant functional traits: leaf nitrogen content (leaf N), specific leaf area (SLA), wood density and bark thickness. We observed significant shifts in forest composition, structure, CWM traits and functional diversity from 1880 to 2011. These changes reflect a reduction in fire and drought tolerance, driven largely by increases in the relative importance of Abies concolor and Pinus strobiformis . Compositional changes were associated with declines in CWM leaf N, SLA, wood density and bark thickness. We found lower multitrait functional diversity (Rao's Q) in contemporary forests driven primarily by leaf N; however, bark thickness variation was greater in contemporary forests than in 1880. Synthesis and applications . Compositional shifts towards reduced average bark thickness and wood density in contemporary forests driven by land‐use change have likely reduced forest resilience to both fire and drought. Managers can manipulate forest structure and species composition to achieve functional objectives by increasing stand‐level bark thickness to promote fire tolerance and increasing stand‐level wood density to promote drought tolerance. Forecasts for extended fire seasons along with declining precipitation are projected for many ecosystems around the planet. A focus on restoring optimal functional trait combinations may be as important as managing ecosystem structure for restoring resilient ecosystems. Abstract : Compositional shifts towards reduced average bark thickness and wood density in contemporary forests driven by land‐use change have likely reduced forest resilience to both fire and drought. Managers can manipulate forest structure and species composition to achieve functional objectives by increasing stand‐level bark thickness to promote fire tolerance and increasing stand‐level wood density to promote drought tolerance. Forecasts for extended fire seasons along with declining precipitation are projected for many ecosystems around the planet. A focus on restoring optimal functional trait combinations may be as important as managing ecosystem structure for restoring resilient ecosystems.